Thai EFL teachers and learners’ beliefs and readiness for autonomous learning - Chamaipak Tayjasanant,; Sumittra Suraratdecha, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The emergence of the ASEAN Economic Community has spurred countries in the region to relook their English language teaching approaches to ensure it is in line with regional and global changes. This has resulted in Asian countries seeking to modernise their teaching and learning of the language to promote higher order thinking skills and pave the way for better learner autonomy. This paper examines Thai teacher and learner beliefs about autonomous learning within the Thai culture of learning to determine if both are ready for autonomous learning. Using a qualitative approach employing interviews with teacher and students data was created from 76 English language teachers and 116 lower secondary school students, subdivided into high performing and low performing groups from 41 schools in Bangkok. The overall results indicate that both teachers and students hold positive beliefs about autonomous learning. The findings further reveal that the teachers supported communicative language learning while the students emphasised their needs for mental support, that teachers from large schools have higher academic expectations than those from smaller schools, and that lower performing students struggle for more academic and psychological support than their higher performing peers. The exam system, students’ dependence on teachers, and a lack of understanding from families and surrounding communities make it difficult for both teachers and students to achieve a high degree of autonomy. The study sheds some light on the challenges facing policy makers, particularly the Ministry of Education, with regard to what they can do to promote autonomy in the Thai school system.